2023
DOI: 10.3389/fnut.2022.1087453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate how steaming and sulfur fumigation change the microstructure, physicochemical properties and in vitro digestibility of Gastrodia elata Bl. starch

Abstract: The sulfur dioxide gas (SO2) generated by sulfur burning can improve the appearance quality of food and enhance the storage time. However, excessive sulfur dioxide will pollute the environment and cause deterioration of food quality, and even the high residual levels can increase the risk of cancer. As Gastrodia elata Blume is prone to corruption during processing, sulfur fumigation is often used for preservation. In this study, spectral analysis and Texture Profile Analysis (TPA) were used to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The long branching chain of amylopectin could also mimic amylose and stretch to support the integrity and stability of the whole particle structure, thereby inhibiting the gelatinization of starch [ 21 ]. Guan et al [ 22 ] found that compared with non-steamed G. elata , the content of amylose in steamed G. elata increased by 1.08-times that of amylopectin, and the degree of molecular crosslinking was increased by steaming. These results might also indicate that G. elata amylopectin was starch with high branching degree but a short branching chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long branching chain of amylopectin could also mimic amylose and stretch to support the integrity and stability of the whole particle structure, thereby inhibiting the gelatinization of starch [ 21 ]. Guan et al [ 22 ] found that compared with non-steamed G. elata , the content of amylose in steamed G. elata increased by 1.08-times that of amylopectin, and the degree of molecular crosslinking was increased by steaming. These results might also indicate that G. elata amylopectin was starch with high branching degree but a short branching chain.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the molecular chain of amylopectin broke and generated short amylose. The short amylose pulled the broken amylopectin molecules and the original amylose molecules together through hydrogen bonds, forming a complex dense network structure (as shown in Figure 6C,M), which increased the molecular cross-linking degree and, thus, hindered the flow of water [ 22 ]. In addition, the high-viscosity starch also covered the surface of the dry material, which was additional resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Slowing down respiration and transpiration is an effective approach to preserve the quality of fresh-cut fruits and vegetables. Melatonin is a vital hormone in the human body that plays a crucial role in regulating the biological clock and sleep cycles [ 2 ]. However, its presence in plants is typically in trace amounts, serving as a natural plant signaling molecule, and generally does not have adverse effects on human health [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, G. elata was designated as a pilot variety for the homology of medicine and food by the Chinese health commission. With G. elata being recognized as a food with medicinal properties, its applications as a food with medicinal properties are rapidly expanding [ 2 ]. Storing fresh G. elata for extended periods is challenging, and it is prone to rot [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 C). During the steaming process, starch absorbs water, expands, and breaks, releasing a large amount of amylose ( Guan et al, 2022 ). Starch is comprised of two components, namely amylopectin and amylose.…”
Section: Resultsmentioning
confidence: 99%